Effectiveness of Interactive Classroom Tool: A Quasi-Experiment in Assessing Students’ Engagement and Performance in Mathematics 10 using ClassPoint - Doris V Querido; Alberto D Yazon; Karen A Manaig; Victoria E Tamban; Sherwin B Sapin (Research Synergy Foundation, 2023)
Concerns about students' math skills have long existed on a global scale, the Philippines performed